2021
DOI: 10.3389/fpsyg.2020.568586
|View full text |Cite
|
Sign up to set email alerts
|

Good News or Bad News? How Message Framing Influences Consumers’ Willingness to Buy Green Products

Abstract: Despite the growing social interest in green products, companies often find it difficult to find effective strategies to induce consumers to purchase green products or engage in other environmentally friendly behaviors. To address this situation, we examined the favorable or unfavorable effects of positive and negative message frames on consumers’ willingness to consume green products in different psychological distance contexts. Through two Studies, we found that the positive information framework played a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…In contrast, information about green behaviors such as energy saving or other proenvironmental consumption alternatives spread through media channels, including social network, is confirmed to attract more proenvironmental behaviors (Li et al. , 2019; Tong et al. , 2020).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, information about green behaviors such as energy saving or other proenvironmental consumption alternatives spread through media channels, including social network, is confirmed to attract more proenvironmental behaviors (Li et al. , 2019; Tong et al. , 2020).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 92%
“…The moderating effects in the relationship between subjective well-being and PECB When it comes to environmental messages, the diffusion of negative messages about environmental damages on media channels has been reported to discourage people's participation in green behaviors (Li et al, 2018). In contrast, information about green behaviors such as energy saving or other proenvironmental consumption alternatives spread through media channels, including social network, is confirmed to attract more proenvironmental behaviors (Li et al, 2019;Tong et al, 2020). This research focuses on positive messages or information about green behaviors, green alternatives or choice of PECB that are communicated and spread on different types of media such as TV, newspapers, the Internet and social networking sites.…”
Section: 5mentioning
confidence: 99%
“… Tong et al (2020) and Khalil et al (2022) emphasize the positive emotional impact of portraying solution-orientated sustainable behaviors and their positive outcomes. Increased motivation, engagement, and willingness to adopt sustainable behaviors are potential effects ( Ojala, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, to determine whether the lack of effect is attributable to the initially high levels of responsibility scores or the perceived distance to pre-produced materials, further studies need to be conducted. Tong et al (2020) and Khalil et al (2022) emphasize the positive emotional impact of portraying solution-orientated sustainable behaviors and their positive outcomes. Increased motivation, engagement, and willingness to adopt sustainable behaviors are potential effects (Ojala, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Hotspot 1 focused on the drivers of psychological distance of environmental change perception on citizen environmental behavior. Western society has become increasingly concerned about the harm caused by some products to the environment, and many consumers have begun to change their purchasing behavior and support producers selling organic products or participating in green policies (De Maya et al, 2011;Tong et al, 2020). De-Magistris and Gracia (2016) used a non-hypothetical evaluation method to simulate the real market with real products and money and found that consumers were more willing to accept sustainable consumption in order to reduce greenhouse gas emissions.…”
Section: High Frequency Keyword Feature Analysismentioning
confidence: 99%